IDENTIFIKASI BAHAN TAMBAHAN MAKANAN (BTM) DI PASAR CIMAHI TENGAH IDENTIFIKASI BAHAN TAMBAHAN MAKANAN (BTM) DI PASAR CIMAHI TENGAH - Febrianti, Vina; Nindy M, Deita; Al Jinatul A, Azizah; Rofiqoh, Wafa; Ramadhan B, Rizqi; Fitriana, Selma; Purnama, Aldi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2023)
The easy access to food additives in Central Cimahi has made a number of traders add additives to food sold for consumption in order to increase profits. On the other hand, the use of inappropriate food additives can damage health. Formalin, borax and Rhodamine B dye are chemical compounds that provide many benefits to life, borax is useful for preserving wood and cleaning agents, while formalin is a preservative for corpses and is carcinogenic which can trigger cancer if consumed. Meanwhile, Rhodamine B dye is actually used for textile dyes. Therefore, these chemicals are prohibited for consumption. If this compound is consumed, it will become very dangerous and deadly. Nowadays, street food is loved by many people and there are even cases of fraudulent sellers by adding borax, formalin and Rhodamine B. This study aims to review the literature to prove whether there are snack foods that contain formalin, borax and Rhodamine B which can harm human health and provide knowledge to the public about the dangers of these chemicals and how to sort healthy foods and avoid the following substances.